Implikasi Peer Group Terhadap Perilaku Kriminalitas Yang Dilakukan Oleh Anak Berkonflik Dengan Hukum - Rama Maulana Nurwahyudin; Wahyu Febriansyah; Ikawati Ratnaduhita; Wiji Aulia Fatihah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Adolescent delinquency behavior often stems from teenagers' involvement with peer groups at school or in the educational environment. This can develop into more serious criminal behavior later on. Adolescents engaged in delinquent behavior can be categorized as Juvenile Offenders (JO). Peer groups provide a social environment in which JOs can learn and develop various aspects of themselves; however, they also serve as a primary source of negative influence. Similar habitus within social groups reinforce solidarity and camaraderie within them, which may be a reason for teenagers to join peer groups from the same social class. This also provides a sense of comfort and acceptance, while joining groups from different social classes can lead to feelings of inferiority and inequality. Thus, peer groups can have both positive and negative implications depending on the social conditions within a peer group.